Laure Moghaizel - Aghacy, Samira (1998)
Many of us will always remember Laure Moghaizel's funeral , and the sight of her coffin carried over the shoulders of women into Sayyidat al-Mukhallis Church in Beirut, an unprecedented though very telling act that sums up the feelings of love, gratitude and loss that most Lebanese women felt on the death of this remarkable woman